Assessing the sustainability capacity of evidence-based programs in community and health settings - Bacon, Caren; Malone, Sara; Prewitt, Kim; Hackett, Rachel; Hastings, Molly; Dexter, Sarah; Luke, Douglas A. (Frontiers in Health Services, 2022)
Background Within many public health settings, there still remain large challenges to sustaining evidence-based practices. The Program Sustainability Assessment Tool has been developed and validated to measure sustainability capacity of public health, social service, and educational programs. This paper describes how this tool was utilized between January 2014 and January 2019. We describe characteristics of programs that are associated with increased capacity for sustainability and ultimately describe the utility of the PSAT in sustainability research and practice. Methods The PSAT is comprised of 8 subscales, measuring sustainability capacity in eight distinct conceptual domains. Each subscale is made up of five items, all assessed on a 7-point Likert scale. Data were obtained from persons who used the PSAT on the online website (https://sustaintool.org/), from 2014 to 2019. In addition to the PSAT scale, participants were asked about four program-level characteristics. The resulting dataset includes 5,706 individual assessments reporting on 2,892 programs. Results The mean overall PSAT score was 4.73, with the lowest and highest scoring subscales being funding stability and program adaptation, respectively. Internal consistency for each subscale was excellent (average Cronbach’s alpha = .90, ranging from .85 to .94). Confirmatory factor analysis highlighted good to excellent fit of the PSAT measurement model (eight distinct conceptual domains) to the observed data, with a comparative fit index of .902, root mean square error of approximation equal to .054, and standardized root mean square residual of .054. Overall sustainability capacity was significantly related to program size (F = 25.6; p < .001). Specifically, smaller programs (with staff sizes of ten or below) consistently reported lower program sustainability. Capacity was not associated with program age and did not vary significantly by program level. Discussion The PSAT maintained its excellent reliability when tested with a large and diverse sample over time. Initial criterion validity was explored through the assessment of program characteristics, including program type and program size. The data collected reinforces the ability of the PSAT to assess sustainability capacity for a wide variety of public health and social programs.